'Compiled from Official Records': Mapping Kansas Territory before the Civil War. Issue Volume 74:Issues 1(2022) (2nd January 2022) - Grim, Ronald E.
ABSTRACT: Tension between pro- and anti-slavery factions during the delineation and mapping of Kansas Territory in the 1850s, as Euro-American settlement moved west of the Mississippi River, permeated local politics and commerce. Despite the standardized surveying system employed by the U. S. General Land Office, this tension was reflected in township or sectional state maps that were produced during this time period. Using government surveys and reports documenting the progress of township surveys, commercial map publishers and land agents produced maps with the purpose of promoting quick land sales and profits. Yet the profit motive is not the only one apparent in these maps, and the history of their production is rife with intriguing stories involving conflicts of interest for government employees and the pro- and anti-slavery politics that dominated this critical period in U. S. history.